2019
DOI: 10.1016/j.biopsych.2019.06.011
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Microstructure and Its Relation to Longitudinal Measures of Depressive Symptoms in Mid- and Late Life

Abstract: BackgroundStudies of white matter microstructure in depression typically show alterations in individuals with depression, but they are frequently limited by small sample sizes and the absence of longitudinal measures of depressive symptoms. Depressive symptoms are dynamic, however, and understanding the neurobiology of different trajectories could have important clinical implications.MethodsWe examined associations between current and longitudinal measures of depressive symptoms and white matter microstructure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 57 publications
4
19
0
Order By: Relevance
“…For example, DS from both reports was significantly associated with global cortical volume (caregiver: β = −0⋅037; child: β = −0⋅027) and surface area (caregiver: β = −0⋅034; child: β = −0⋅020), while MDD status was associated with decreased whole brain FA (caregiver: β = −0⋅030; child: Cohen's d = −0⋅021). The effect sizes were similar to those found in adults [6] . However, the current study also revealed that reports of depression by caregivers on adolescents demonstrated stronger and more numerous associations with brain structural measures than by adolescent self-report.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…For example, DS from both reports was significantly associated with global cortical volume (caregiver: β = −0⋅037; child: β = −0⋅027) and surface area (caregiver: β = −0⋅034; child: β = −0⋅020), while MDD status was associated with decreased whole brain FA (caregiver: β = −0⋅030; child: Cohen's d = −0⋅021). The effect sizes were similar to those found in adults [6] . However, the current study also revealed that reports of depression by caregivers on adolescents demonstrated stronger and more numerous associations with brain structural measures than by adolescent self-report.…”
Section: Discussionsupporting
confidence: 85%
“…Adolescent depression is notably associated with a more severe illness course and can lead to the propagation of difficulties across the lifespan [4] . MDD is associated with disruptions in brain structure [5] , [6] , [7] , [8] . However, due to a lack of large-scale neuroimaging samples for adolescents, the origin and development of depression-related imaging features remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with previous research showing that participants with BD II/NOS, compared to HC, had significant reductions in FA in the major white matter tracts 31 , and that white matter microstructure in the anterior thalamic radiation connecting thalamus to the frontal cortex 64 and arcuate fasciculus connecting temporal and parietal cortices to the frontal cortex 65 was associated with depressive symptoms. The frontal aslant tract connects the posterior part of the inferior frontal gyrus with supplementary and pre-supplementary motor areas 66 and is frequently associated with speech, language, and verbal fluency 67 , 68 .…”
Section: Discussionsupporting
confidence: 92%
“…Parameters of water diffusion in white matter derived from diffusion-weighted imaging (DWI), such as fractional anisotropy (FA), mean, axial, and radial diffusivity (MD, AD, and RD) are well-established markers of normal brain maturation (1)(2)(3)(4)(5) and ageing (6)(7)(8)(9)(10)(11)(12) and have been proposed as potential tools for the investigation of various brain disorders (13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%